Boranil dyes bearing tetraphenylethene: Synthesis, AIE/AIEE effect properties, pH sensitive properties and application in live cell imaging. Issue 27 (4th July 2018) - Chen, Shengxin; Qiu, Rongmao; Yu, Qiuhan; zhang, Xueyan; Wei, Ming; Dai, Zhenya
Graphical abstract: A family of new boranil dyes was prepared by three-step procedures. All the dyes exhibit large stokes shift (more than 5000 cm −1 ). Dye 9 exhibits AIE/AIEE effect in MeCN/water solution when the water fraction increases to 80%. Dye 8 and 10 show pH sensitive properties and can be used for cell imaging. Highlights: Novel sensors 7 –10 were synthesized and characterized. The sensors exhibited large stokes shifts. The sensors could be applied as fluorescent imaging probes. Abstract: A serial of novel fluorescent boranil dyes (7, 8, 9, 10 ) bearing tetraphenylethene were prepared through an efficient process. These dyes exhibited large stokes shifts (more than 5000 cm −1 ) and moderate fluorescent quantum yield from 0.22–0.53. Dye 9 exhibited AIE/AIEE and exhibited weak fluorescence in pure MeCN or the MeCN/water mixture with a water fraction below 80%, in which a significant AIEE effect was observed in the mixture with 80% of water fraction and a sharp increasement in fluorescence intensity was also observed. And dye 8 and 10 showed moderate solvatochromism with the solvent changed from toluene to DMSO, and they displayed sensitivities to pH change in MeCN/water solution. Interestingly, dyes 8 and 10 obtained by column chromatography and slow solvent evaporation showed different X-ray diffraction properties. Moreover, compound 8 and 10 could be applied to cell imaging.